Mycotoxins presence in pre- and post-fermented silage from Tunisia - C. Juan; A. Mannai; H. Ben Salem; S. Oueslati; H. Berrada; A. Juan-García; J. Mañes (Arabian Journal of Chemistry, 2020)
Silage represents a major part of the feed ration for livestock, being a potential cause of mycotoxicosis as it can be contaminated with toxigenic fungi capable of producing mycotoxins in suitable environmental conditions.In the present work, the presence of natural mycotoxins in samples collected of silage from the main producing areas in Tunisia (Ariana, Bizerte, Béjà and Jendouba) was assessed based on different plant material (oat, barley, triticale, artichoke, sulla or raygrass). Mycotoxins were evaluated during three periods in green forage (P1) and subsequently in ensiled products after 60 days (P2) and 100 days (P3) of fermentation. Samples were extracted by a QuEChERS procedure and analyzed by mass spectrometry for the determination of 23 mycotoxins. The results showed the presence of Fusarium mycotoxins, deoxynivalenol (DON), HT-2 toxin, zearalenone (ZEA), enniatins (ENA1, ENB, ENB1) and beauvericine (BEA); as well as one Alternaria mycotoxin tentoxin (TENT). The highest values detected were for DON in the three periods. DON maximum value were 381, 2053 and 916 µg/kg for P1, P2 and P3, respectively. This study demonstrated the presence of fungi and DON, ZEA and ENs contamination in Tunisian silage without a recognized risk on the ruminants or further in humans. However, a continuous enhancement of the silage quality, and management and control of mycotoxins, should be implemented to ensure safe ensilable plant material.